2021
DOI: 10.3389/fmicb.2021.706647
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Antifungal Actinomycete Streptomyces sp. Strain H3-2 Effectively Controls Banana Fusarium Wilt

Abstract: Banana Fusarium wilt disease caused by Fusarium oxyspoum f. sp. cubense (Foc) seriously threatens the banana industry. Foc tropical race 4 (Foc TR4) can infect almost all banana cultivars. Compared with traditional physical and chemical practices, biocontrol strategy using beneficial microbes is considered as an environmentally sound option to manage fungal disease. In this study, a strain, H3-2, isolated from a non-infected banana orchard, exhibited high antifungal activity against Foc TR4. According to its m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…The results hinted at complete collapse and degeneration of spores due to decreased exopolysaccharide formation in outer membrane (Li et al 2021). Another study reported the morphology of treated hypha showing exfoliated akes, shrivelling, vacuolation and blistering; thickened cell wall and septum with partly ruptured cell membrane along with swollen cell nucleus was also observed (Zou et al 2021).…”
Section: )mentioning
confidence: 99%
“…The results hinted at complete collapse and degeneration of spores due to decreased exopolysaccharide formation in outer membrane (Li et al 2021). Another study reported the morphology of treated hypha showing exfoliated akes, shrivelling, vacuolation and blistering; thickened cell wall and septum with partly ruptured cell membrane along with swollen cell nucleus was also observed (Zou et al 2021).…”
Section: )mentioning
confidence: 99%
“…The PDA plates were incubated at 28 °C for 5 days. The inhibition rate (IR) was calculated according to Zou et al 10 Based on the inhibition rate against Foc TR4, an isolate, labeled as strain 2−11, with strong antifungal activity was selected for the following study. Twelve phytopathogenic fungi were chosen to further analyze the broad-spectrum antifungal activity of strain 2−11 (Table S1).…”
Section: Isolation Of Actinobacteria a Soft Coral (Menella Woodin)mentioning
confidence: 99%
“…Effect of Niphimycin C on the Hyphal Morphology of Foc TR4. The hyphal morphology of Foc TR4 was determined according to Zou et al 10 Briefly, Foc TR4 was inoculated onto the PDA plate containing 2 × EC 50 of niphimycin C and incubated at 26 °C for 3 days. The control plate contained 10% (v/v) DMSO.…”
Section: Effect Of Niphimycin C On the Spore Morphology Of Foc Tr4mentioning
confidence: 99%
See 2 more Smart Citations